Facile Access to Spiro[4.5]decanes through Oxidative Dearomatization-Induced Ring Expansion of Cyclobutanes - Xi, Shuang; Zhang, Jingyang; Guo, Zhen; Zu, Yumeng; Liu, Yang; Wang, Gelin; Tang, Yefeng (Synthesis, 2022)
A mechanistically interesting and practical method for the synthesis of functionalized spiro[4.5]decanes is developed, featuring oxidative dearomatization-induced ring expansion of cyclobutanes as the key element. The new method enables facile access to a variety of spiro[4.5]cyclohexadienones with good efficiency and generality. Further elaboration of the resulting products into other valuable scaffolds is also explored, leading to the discovery of an interesting compound that displays a promising biological profile. Moreover, we have also conducted a comprehensive computational study that provides a deep insight into the mechanism of the reaction.
Keywords: oxidative dearomatization; phenol; cyclobutane; ring expansion; spiro[4.5]decane